Monitoring area screening of AC system to improve embedded VSC‐HVDC operation efficiency. Issue 6 (30th December 2020) - Lee, Jaehyeong; Kim, Woosung; Jung, Seungmin; Suh, Jaewan; Yoon, Minhan; Jang, Gilsoo
Abstract: With the increasing number of embedded high‐voltage DC (HVDC) projects in AC systems, there is growing research interest in controlling the operating point of the HVDC in real time. This real‐time operation system requires the AC system information to be continuously updated, which involves practical challenges such as the burden of communication. To mitigate this problem, this paper proposes a novel technique to screen the AC system monitoring area for the efficient operation of the embedded HVDC. The screening algorithm determines the monitoring area by HVDC sensitivity analysis using the power transfer distribution factor. Then, a reliable and efficient grid operation is enabled using the limited data obtained from the determined area. The proposed methodology is verified using a Korean power system with multiple HVDCs. The effectiveness and advantages of the proposed technology are verified by comparing the results obtained using the system‐wide data with those obtained from the monitoring area.